2016
DOI: 10.1093/ijnp/pyw103
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Ameliorates Homocysteine-Induced Cognitive Dysfunction by Inhibition of Reactive Aldehydes Involving Upregulation of ALDH2

Abstract: Background:Homocysteine, a risk factor for Alzheimer’s disease, induces cognitive dysfunction. Reactive aldehydes play an important role in cognitive dysfunction. Aldehyde-dehydrogenase 2 detoxifies reactive aldehydes. Hydrogen sulfide, a novel neuromodulator, has neuroprotective effects and regulates learning and memory. Our previous work confirmed that the disturbance of hydrogen sulfide synthesis is invovled in homocysteine-induced defects in learning and memory. Therefore, the present work was to explore w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…Our previous studies have demonstrated that H 2 S has a protective effect against Hcy-evoked neurotoxicity [20,[24][25][26]. Considering the cellular senescence is prominent in the neurotoxicity of Hcy [3,[27][28][29], the present work was designed to explore whether the protection of H2S against the neurotoxicity of Hcy is associated with regulating neuronal senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that H 2 S has a protective effect against Hcy-evoked neurotoxicity [20,[24][25][26]. Considering the cellular senescence is prominent in the neurotoxicity of Hcy [3,[27][28][29], the present work was designed to explore whether the protection of H2S against the neurotoxicity of Hcy is associated with regulating neuronal senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Sniffing and touching of the objects (distance within 1 cm) were considered exploratory behaviors, whilst climbing on the objects or chewing were not. Discrimination index, which was calculated as the time difference between new and familiar object exploration/total time, was adopted to evaluate animal cognitive function (21,22). Y-maze test.…”
Section: Animalsmentioning
confidence: 99%
“…Accumulating evidences demonstrate that H 2 S facilitates the induction of hippocampal long term potentiation (LTP) [ 8 , 9 ] and attenuates hepatic I/R- or β-amyloid-induced impairment in spatial learning and memory [ 10 - 13 ]. Moreover, our recent study certified that disturbance of endogenous H 2 S generation in hippocampus is involved in deficits in learning and memory [ 14 , 15 ] and that H 2 S antagonizes formalydehyde-exerted deficits in cognitive function [ 16 ]. Thus, the present work was to explore whether H 2 S ameliorates CRS-induced cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%